Job Stress and Lecturers’ Efficiency in Obafemi Awolowo University, Ile-Ife, Nigeria - Ajadi, Olugbenga (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The roles of lecturers in universities cannot be under-estimated. This is because lecturers are the bones who interpret the content of the curriculum and ensure students become a law abiding and useful member in the society. Hence, lecturers are expected to be efficient. This study however investigated job stress and lecturers’ efficiency in Obafemi Awolowo University, Ile-Ife, Nigeria. The population of the study comprised all academic staff in all the 10 Faculties and two Colleges of the University. A sample of 50 participants was selected from each of the five purposively selected faculties making a total of 250 participants altogether. Adapted questionnaire titled titled ‘Job Stress and Lecturers’ Efficiency (JSLEQ) was used to collect information from the respondents. The instrument was validated and trial tested on population outside the sample. The reliability index of the instrument was 0.91 using Crobatch Alpha method of analysis. Descriptive and inferential statistics were used to answer the research question and test the hypothesis respectively. The results showed that anxiety ( = 2.92) was the most prominent stress of the six-stress found among lecturers in Obafemi Awolowo University while the least prominent stress was heart palpitation ( = 2.69). In addition, the results revealed that stress has significant influence on lecturer’s efficiency (0.54 > 0.157 at p.<0.05) in Obafemi Awolowo University, Ile-Ife, Nigeria. The study recommends employment of seasoned counsellors and equip the counselling unit with 21st century equipment that can be used to manage anxiety among the entire workers in the Nigerian universities